2020
DOI: 10.18632/aging.202284
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of lncRNA MIAT alleviates LPS-induced pneumonia via regulating miR-147a/NKAP/NF-κB axis

Abstract: Purpose: Pneumonia is a respiratory disease with an increasing incidence in recent years. More and more studies have revealed that lncRNAs can regulate the transcriptional expression of target genes at different stage. Herein, we aimed to explore the effect of lncRNA MIAT in LPS-induced pneumonia, and further illuminate the possible underlying mechanisms. Method and results: Mice were intraperitoneally injected with LPS, and the lung inflammation was evaluated. Microarray showed lncRNA MIAT was up-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…In cancer-related studies, miR-147a has been identified as a tumor suppressor to regulate cancer progression, such as non-small-cell lung cancer [ 24 ] and cervical cancer [ 25 ]. MiR-147a might inhibit cellular inflammation to mitigate pneumonia process [ 26 ]. Ji et al .…”
Section: Discussionmentioning
confidence: 99%
“…In cancer-related studies, miR-147a has been identified as a tumor suppressor to regulate cancer progression, such as non-small-cell lung cancer [ 24 ] and cervical cancer [ 25 ]. MiR-147a might inhibit cellular inflammation to mitigate pneumonia process [ 26 ]. Ji et al .…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between miRNAs and lncRNAs is indispensable in the development of diseases ( 32 , 35 , 36 ). Tang et al ( 26 ) reported that as the ceRNA for miR-20b-5p, HOTAIR knockdown attenuates autophagy in hepatic I/R injury by improving the inhibitory effect of miR-20b-5p on ATG7.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging pieces of evidence on the pathophysiology of non-coding RNAs in infectious diseases have been published recently [ 31 ]. For instance, elimination of MIAT suppressed cell apoptosis, and ultimately protect the balance of lung function via miR-147a/NKAP crosstalk [ 32 ]. Besides, SNHG16 partially restores the damage of LPS in A549 cells on the aspects of cell viability, inflammation, and apoptosis [ 33 ] Interference of circ-0059930 can notably improve proliferation and inhibit apoptosis of LPS-induced MRC-5 cells [ 34 ].…”
Section: Discussionmentioning
confidence: 99%